Peran Sustainability Report Dalam Memoderasi Pengaruh Green Accounting Dan Kinerja Keuangan Terhadap Nilai Perusahaan - Rahmadani, Sri Ayu Dwi; Susilowati, Endah (Universitas Gorontalo, 2025)
This research aims to examine the role of environmental sustainability reports in moderating the impact of green accounting and financial performance on firm value. The secondary data used were obtained from company reports on idx.co.id and official corporate websites. The Partial Least Squares (PLS) analysis approach was employed using SmartPLS software. The results indicate that green accounting does not affect firm value, financial performance influences firm value, environmental sustainability reporting affects firm value, environmental sustainability reporting moderates the relationship between green accounting and firm value, environmental sustainability reporting does not moderate the relationship between financial performance and firm value.